Industri Pasar Modal Syariah di Malaysia dan Indonesia - Permana, Febrian; Aris, Muhammad; S, Syahpawi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to explain how the development, growth and role as well as the potential for cooperation between Islamic capital markets in Malaysia and Indonesia. This research includes a literature study, using data collection methods namely browsing files, internet websites, documents and information related to the object of research including relevant books. The result of this research is that there is still uneven understanding and or knowledge of the Indonesian people about investing in sharia-based capital markets, also not supported by adequate regulations on sharia investment in the Indonesian capital market, as well as the assumption that investing in the Islamic capital market requires relatively more expensive costs when compared to investing in other financial sectors. While the Islamic capital market has experienced significant growth, there are still challenges in creating a variety of products and instruments that comply with sharia principles and can fulfil the needs of investors.